2016
DOI: 10.1103/physrevfluids.1.084201
|View full text |Cite
|
Sign up to set email alerts
|

Drying dynamics of a charged colloidal dispersion in a confined drop

Abstract: We performed a thorough investigation of the drying dynamics of a charged colloidal dispersion drop in a confined geometry. We developed an original methodology based on Raman micro-spectroscopy to measure spatially-resolved colloids concentration profiles during the drying of the drop. These measurements lead to estimates of the collective diffusion coefficient of the dispersion over a wide range of concentration. The collective diffusion coefficient is one order of magnitude higher than the Stokes-Einstein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
87
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(96 citation statements)
references
References 48 publications
9
87
0
Order By: Relevance
“…Because of the thin geometry, it has been assumed that suspension ow is almost ideal. However, recent studies have revealed that vertical ows are induced spontaneously, even in a thin liquid layer owing to drying-induced increase in the solute concentration [18][19][20][21] and in the concentration of suspended particles. 22 These examples suggest that ow is complex, even in a drying thin liquid layer between parallel plates.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the thin geometry, it has been assumed that suspension ow is almost ideal. However, recent studies have revealed that vertical ows are induced spontaneously, even in a thin liquid layer owing to drying-induced increase in the solute concentration [18][19][20][21] and in the concentration of suspended particles. 22 These examples suggest that ow is complex, even in a drying thin liquid layer between parallel plates.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13]. We will assume an initial concentration Φ i = 0.001 and radius a = 5 nm for the silica nanoparticles, leading to a diffusivity D 4.37 × 10 −11 m 2 /s according to the Stokes-Einstein relation for a temperature of 25 • C (we do not consider here enhanced values due to colloidal interactions occurring for such systems at high concentrations [4,16]). For such a very dilute silica dispersion, the solutal expansion coefficient at the reference concentration Φ i is well approximated by β s ρ s /ρ w − 1 1.2 where ρ s 2200 kg/m 3 is the density of silica, and ρ w 1000 kg/m 3 that of water.…”
Section: B Numerical Resolution On a Given Experimental Casementioning
confidence: 99%
“…When these gradients are orthogonal to gravity, they inevitably generate buoyancydriven flows, that then alters the drying process when coupled to the overall mass transport. Solutal buoyancy-driven free convection is generally relevant at relatively large scales, but many recent experiments reported such flows in confined microfluidic geometries (10-100 µm): drying of confined [1][2][3][4] and sessile droplets [5][6][7], or any other microfluidic configuration generating concentration gradients [8,9]. At small scales, buoyancy-driven flows are expected to play a minor role on mass transport, owing to the high viscous dissipation and fast solute diffusion [10].…”
Section: Introductionmentioning
confidence: 99%
“…Gravimetric analysis and videography, which record global water loss and film appearance respectively, are most common methods 7 , 17 . Nuclear magnetic resonance profiling (NMR) 11 , Raman microspectroscopy 18 and infrared microscopy 19 can non-destructively measure the distribution of water concentration inside the latex, but lack the resolution to see particles. With microns or sub-micron resolutions, environmental scanning electron microscopy (ESEM), ellipsometry, atomic force microscopy (AFM) were used to detect particles’ packing process, during which particles gathered with their Brownian motions restricted 9 , 20 22 .…”
Section: Introductionmentioning
confidence: 99%